Impact of COVID‐19 on cardiac surgical training: Our experience in the United Kingdom. Issue 8 (19th June 2020) - Shafi, Ahmed M. A.; Atieh, Abed Elfattah; Harky, Amer; Sheikh, Amir M.; Awad, Wael I.
Abstract: The current evolving global pandemic caused by coronavirus disease‐2019 (COVID‐19) has dramatically impacted global health care systems, resulting in governments taking unprecedented measures to contain the spread of the infection, with adaptations by health care organizations. Research into understanding the pathophysiology behind this virus, to ascertain best medical management and treatment, has been accelerated to keep up with the rapidly evolving situation. There has been redeployment of medical and nursing staff to the frontlines and redistribution of health care resources. In addition, the cancellation of elective surgery and centralization of services to treat high‐risk surgical cases will all, undeniably, have an impact on current surgical training with possible future implications. We aim to explore the impact COVID‐19 is having on cardiac surgical training in the UK and what future implications this may have.